Hubungan Diskusi Tutorial dengan Pencapaian Learning Objectives Blok Hematologi Mahasiswa Pendidikan Dokter Fakultas Kedokteran Universitas Sebelas Maret Surakarta - Ibnu Kharisman; Murkati FK UNS; Prihandjojo Andri Putranto (Nexus Pendidikan Kedokteran dan Kesehatan, 2014)
Background: Learning system in university has been transformed from Teacher Centered Learning (TCL) to Student Centered Learning (SCL). In medical education, SCL systems applied by the Problem Based Learning (PBL) method. Learning objectives in tutorial group discussion which is the implementation of PBL method in Sebelas Maret University Faculty of Medicine reflect the National Standard of Competence of Indonesian Medical Doctor that must be achieved by every medical student in Indonesia. As a new program at Sebelas Maret University Faculty of Medicine, tutorial group discussions roles in ushering students to achieve learning objectives is still in doubt. Until now, there has been no research on the effectiveness of a tutorial discussion on Sebelas Maret University Faculty of Medicine therefore authors are interested in doing this research. Methods: This research is an observational analysis research by cross sectional study approaching. The sample of this research is medical student of Sebelas Maret University Medical Faculty who are undergoing Hematology Block. Sample is taken by cluster sampling method, 43 persons randomly taken from 5 tutorial group of discussion. The chosen sample asked to undergo a pretest before first meeting of tutorial group discussion of Hematology Block. After the second meeting, sample then asked to undergo a posttest. The samples point results of pretest and posttest then compared and analyzed with McNemar method. Results: The percentage of learning objectives achievement from pretest is 7,00% and the percentage from posttest is 37,20%. McNemar test shown significant difference with p=0,000 (p<0,05). Conclusion: Tutorial group discussion is related with the achievement of learning objectives in Hematology Block. Keywords: tutorial group discussion, learning objectives, problem based learning